(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2024)
This article presents the results of a study that analyzes the prevalence and factors associated with burnout syndrome among financial sector employees in the city of Guayaquil. Using the Maslach Burnout Inventory (MBI), a widely recognized tool developed by Dr. Christina Maslach, a representative sample of workers was surveyed to assess three dimensions of burnout: emotional exhaustion, depersonalization, and personal fulfillment. The findings reveal that a significant percentage of financial employees in Guayaquil experience high levels of emotional exhaustion and depersonalization, along with low levels of personal fulfillment, indicating a worrying prevalence of burnout in this sector. The prevalence of burnout in this population was 40.4%. Statistically significant relationships were found between the presence of burnout and variables such as age group, number of children, hours of sleep, self-rated physical health and self-rated mental health. It is necessary that both institutions and control agencies take measures that allow an adequate management of burnout syndrome in the city’s financial system.